Investigation of the effectiveness of small scale solar updraft tower using solar simulator - Saadun, Mohd Noor Asril; Che Sidik, Nor Azwadi; Mohd Rosli, Mohd Afzanizam (Penerbit Akademia Baru, 2024)
Unique solar thermal system comprises a solar updraft tower (SUT) power plant. Numerous outdoor experiments are conducted, but they have a number of drawbacks, including the necessity for a lengthy setup period, a substantial financial investment, the possibility that the results may be affected by the weather, and the inability to manipulate the ambient factors. In this study, a laboratory-scale prototype with a square collector measuring roughly 2.27 m2 and a chimney height of 1.5 m was built. This research focuses on finding many essential parameters for a solar updraft tower system by giving a time-dependent real-time sensor readout. With the help of the internet of things (IoT), measuring and monitoring applications underwent pilot testing. The results indicate that as solar energy increases, the collector and chimney temperature and updraft velocity will also increase. Experiments conducted aided in the comprehension of the thermodynamic properties of the solar chimney power plant, serving as the foundation for the construction of a large-scale solar chimney power plant.